Digitalizing Pindang Industry with Business Model Canvas for Sustainable Blue Economy - Setiyowati, Harlis; Harriz, Muhammad Alfathan; Junaedi, Edi; Akbariani, Nurhaliza Vania; Widodo, Suryo (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study aims to design a tailored Business Model Canvas (BMC) for the pindang business in Babat Village, Tangerang, to support the blue economy framework. A qualitative approach was employed, including field surveys, in-depth interviews with stakeholders, and SWOT analysis. The findings highlight strengths such as a loyal local customer base and traditional expertise, as well as opportunities to expand into modern retail and export markets. However, weaknesses like limited product diversification and threats such as fluctuating fish supplies were also identified. The study provides strategic recommendations, including sustainable product innovation, digital technology adoption, and strategic partnership development, to enhance the competitiveness of pindang products while promoting environmental sustainability. Additionally, the integration of information technology is emphasized to optimize supply chain management, improve digital marketing strategies, and enhance customer engagement through e-commerce platforms. This research contributes to the academic discourse on blue economy implementation, business model innovation in traditional industries, and the role of information technology in modernizing small-scale fisheries. It distinguishes itself from other BMC applications in traditional industries by specifically addressing the unique challenges and opportunities in pindang production, particularly within the context of sustainability and digital transformation.